Physicochemical properties of soil at Habla union of Basail upazila in Tangail - Miah, Md Abdullah; Uddin, Nazia; Hoque, Md Mahbubul; Haq, Md Erfanul; Biswas, Ajay Kumar (Asian Journal of Medical and Biological Research, 2017)
An experiment was conducted to examine the physicochemical properties of soil at Habla union under Basail upazila in Tangail based on the BINA (Bangladesh Institute of Nuclear Agriculture) laboratory analysis of physical and chemical parameters during January to March, 2014. Total 30 soil samples from 10 points of Habla union were collected from 0-15 cm, 15-30 cm, and 30-40 cm depth of the soil respectively. To determine the soil texture the results were compared with the standard value of SRDI and BARC. Among the 30 soil samples, 25 soils texture classes were found sandy clay loam, 4 were sandy clay and rest one was clay loam. The comparative analysis showed that the average texture class is sandy clay loam. The bulk density ranged from1.23 to 1.91 g/cm3 for the total samples which leads to decide that bulk density is gradually increasing with soil depth. The moisture percentage at different depth of soil were 39.23 to 57.23 % (for 0-15 cm), 43.02 to 58.35 % (for 15-30 cm) and 42.08 to 58.24% (for 30-45 cm).The pH obtained from soil samples of the study area were 4.66 to 5.55 (for 0-15cm), 5.37 to 6.18(for 15-30cm), 6.33to 6.60 (for 30-45 cm). The percentage of organic matter of the soil samples were 0.55 to 3.97 % (for 0-15cm), 0.55 to 3.24 % (for 15-30cm), 0.69 to 2.28 % (for 30-45cm).The organic matter content in the surface soil is relatively low compared to standard level that decreases steadily with depth. The percentage of nitrogen (N %) was observed in different depth of the soil were 0.078 to 0.126 % (for 0-15 cm), 0.049 to 0.126 % (for 15-30 cm), to 0.074 % (for 30-45 cm) which revealed that the percentages of total nitrogen were fall with the depth compared to standard level. In different depth of soil, it was observed that the level of phosphorus (P) was very low compared to standard level where the phosphorus (P) concentration of the soil samples were 1.18 to 2.90 mg/kg (for 0-15 cm), 1.30 to 9.95 mg/kg (for 15-30 cm), 1.58 to 10.92 mg/kg (for 30-45 cm). On the other hand, it was observed that the sulfur (S) concentration was increased with the depth of soil compared to standard level. The sulfur (S) concentration of the soil samples were 5.21 to 11.98 mg/kg (for 0-15 cm), 5.37 to 14.16 mg/kg (15-30 cm), 9.03 to 15.09 mg/kg (30-45 cm). The potassium (K) concentration of the soil samples were 0.038 to 0.102 mg/kg (for 0-15 cm), 0.031 to 0.90 mg/kg (for 15-30 cm) 0.055 to 0.171 mg/kg (for 30-45 cm), which indicated that the low K content compared to the standard level. The overall physicochemical parameter of soil samples were not optimum for good agricultural production. As we know all the parameters either directly or indirectly influence the soil fertility and productivity. This was probably the reason for low productivity of soil in the study area. Asian J. Med. Biol. Res. December 2016, 2(4): 664-671